2018
DOI: 10.1002/mnfr.201800066
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Prevents the Development of Hypertension Programmed by Maternal Plus Post‐Weaning High‐Fructose Consumption through Modulation of Oxidative Stress, Nutrient‐Sensing Signals, and Gut Microbiota

Abstract: Targeting oxidative stress, nutrient-sensing signals, and gut microbiota by resveratrol might be a useful therapeutic strategy for the treatment of hypertension induced by excessive consumption of fructose in the adult rat offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 33 publications
5
103
0
1
Order By: Relevance
“…Akkermansia muciniphila is a mucin-degrading bacterium, considered by some authors as an important member of the gut microbiota for control of physiological and homeostatic functions during obesity and type 2 diabetes (Everard et al, 2013). Conversely, other studies showed that increased abundance of A. muciniphila is related to hypertension (Tain et al, 2018) and can impair intestinal barrier function after using mucin by these bacteria as a nutrient (Desai et al, 2016). Depletion of the mucus layer by enriched A. muciniphila was associated with higher susceptibility to a gastrointestinal pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Akkermansia muciniphila is a mucin-degrading bacterium, considered by some authors as an important member of the gut microbiota for control of physiological and homeostatic functions during obesity and type 2 diabetes (Everard et al, 2013). Conversely, other studies showed that increased abundance of A. muciniphila is related to hypertension (Tain et al, 2018) and can impair intestinal barrier function after using mucin by these bacteria as a nutrient (Desai et al, 2016). Depletion of the mucus layer by enriched A. muciniphila was associated with higher susceptibility to a gastrointestinal pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal concentrations of acetate, butyrate, and propionate were measured using gas chromatography-mass spectrometry (GCMS-QP2010; Shimadzu, Kyoto, Japan) with flame ionization detector (FID) [26]. Analytical standard grades of acetate, propionate (both from Sigma-Aldrich, St. Louis, MO, USA), and butyrate (from Chem Service, West Chester, PA, USA) were used as internal standards.…”
Section: Gas Chromatography-flame Ionization Detector (Gc-fid)mentioning
confidence: 99%
“…Simple centrifugation processing was carried out to removes impurity, proteins, and other organic compounds. As described previously [26], all polymerase chain-reaction amplicons were mixed together for sequencing using an Illumina Miseq platform (Illumina, CA, USA) at the Genomic and Proteomic Core Laboratory, Kaohsiung Chang Gung Memorial Hospital (Kaohsiung, Taiwan). Amplicons were prepared according to the 16S Metagenomics Sequencing Library Preparation protocol (Illumina, CA, USA), and sequenced the variable V3-V4 regions of the 16S rRNA gene with the Illumina MiSeq platform (Illumina, CA, USA) in paired-end mode with 600-cycle sequencing reagent.…”
Section: Analysis Of Gut-microbiota Compositionmentioning
confidence: 99%
See 2 more Smart Citations